A REVIEW OF SUPPLY CHAIN MANAGEMENT LITERATURE AND ITS IMPLICATION TO DEVELOP AGRIBUSINESS IN INDONESIA - Yanti Nuraeni Muflikh; Suprehatin Suprehatin (Departemen Agribisnis, FEM-IPB, 2009)
Supply chain management has been a popular issues and an interesting discussion topic. It can be seen that many research has been done by academia, researcher, practitioners and policy makers through scientific publication, scientific meeting, and professional development program and course development in university. However, within the SCM studies there is a great diversity of concept and definitions of what constitutes a SCM. This paper is based on literature review with highlited the important to build and develop sustainable SCM. This paper discuss the driving forces of SCM, the concepts and theories related to SCM, the framework to develop SCM, the dimension of SCM and its implications to develop agribusiness in Indonesia.